Cell wall surface properties and flocculence of a Kluyveromyces marxianus strain - Teixeira, J. A. (1995)
Yeast flocculation is under genetic control and is described as a cell wall interaction. This characteristic of yeast cells has been traditionally used in industrial fermentation processes. The surface characteristics of the cell walls are expected to be a determinant factor in the aggregation mechanism. Results confirming this have been reported for Saccharomyces strains. It is important to extend these studies to other genera. Among them, due to its potential industrial interest, Kluyveromyces strains must be considered. In this work are reported results relating cell wall surface properties (hydrophobicity and electrophoretic mobility) with the flocculation ability of a strain of Kluyveromyces marxianus. The effect of proteolytic enzymes, pH, salts and sugars on flocculation was also studied. The results obtained clearly demonstrate that cell wall hydrophobicity is a major determinant in the flocculation ability of the Kluyveromyces marxianus cells.